2016
DOI: 10.1017/s1368980016002603
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between micronutrient status and sleep patterns: a systematic review

Abstract: Objective To review articles on the relationship of dietary and circulating micronutrients with sleep patterns, and to identify issues surrounding implications for future research and public health practice. Design A systematic review was conducted. PubMed, Embase and Scopus were searched through January 2016. Setting Both experimental and observational studies were included. However, studies that focused on secondary sleep impairment due to comorbidities were excluded. Subjects Individuals in different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 74 publications
0
49
1
3
Order By: Relevance
“…Clearly, further research is needed on individuals with suboptimal rather than acute nutritional shortfalls to see if such inter-associations still exist and in relation to the potential role(s) of other micronutrients. Other recent work has found that nutrients such as iron, zinc, and magnesium are positively associated with sleep duration with potential mechanisms appearing to involve the effects that micronutrients have on neurotransmitters and the expression of circadian genes ( 46 ). Ongoing work is undoubtedly needed to monitor the ramifications of ongoing food trends, food fortification, and updated public policies.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Clearly, further research is needed on individuals with suboptimal rather than acute nutritional shortfalls to see if such inter-associations still exist and in relation to the potential role(s) of other micronutrients. Other recent work has found that nutrients such as iron, zinc, and magnesium are positively associated with sleep duration with potential mechanisms appearing to involve the effects that micronutrients have on neurotransmitters and the expression of circadian genes ( 46 ). Ongoing work is undoubtedly needed to monitor the ramifications of ongoing food trends, food fortification, and updated public policies.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Sleep is a crucial lifestyle factor that has only recently begun to draw attention in research and practice. Optimal sleep patterns have a tangible impact on chronic physical and psychological disorders [1], with poor sleep quality being related to depression, cardiometabolic disorders, cardiovascular disease and cancer incidence as well as elevated mortality rates [2][3][4][5][6][7][8]. Sleep accounts for one-third of an individual's lifetime, with 7-8 h being the optimal daily duration for most age groups, as recommended by the National Sleep Foundation [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a global epidemic of sleep disorders has emerged [14]. Given that those disorders are highly prevalent and carry negative impacts on general health, modifiable risk factors need to be uncovered, which can be used for prevention [1].…”
Section: Introductionmentioning
confidence: 99%
“…The reciprocal relationship between sleep and diet in humans has been studied since the 1980s [30,31,32]. Sleep disruption affects dietary intake [29,33,34] and dietary intake affects sleep [2,35,36]. With the reciprocal relationship in mind, The World Health Organization (WHO) recommends consuming 400 g or more of FV per day to improve overall health and reduce the risk of chronic diseases [37].…”
Section: Introductionmentioning
confidence: 99%